Chronic autoimmune gastritis and its relation to megaloblastic anemia – Main histopathological and pathophysiological characteristics (International Seven Journal of Health Research, 2024)
Chronic autoimmune gastritis is a sustained inflammation of the stomach, characterized by being immunologically mediated against intrinsic factor-producing parietal cells, leading to nutritional deficiencies that may result in anemia. This study investigates the prevalence and underlying mechanism of anemia in patients with chronic autoimmune gastritis, focusing on iron deficiency anemia and megaloblastic anemia due to vitamin B12 deficiency. A bibliographic review was carried out on the subject, in databases of scientific relevance and verified by peers, whose inclusion criteria allowed only studies relevant to the subject, published in the last five years, which establish a relationship with chronic autoimmune gastritis and anemia. Thus, the exclusion criteria left out studies on chronic gastritis due to other etiologies, those cases not related to anemia, or other studies not relevant to the general objective. In the pathophysiological framework, there is an autoimmune destruction of gastric parietal cells, which leads to a reduction in the secretion of hydrochloric acid and intrinsic factor, essential for the absorption of vitamin B12 and iron, predisposing to iron deficiency and megaloblastic anemia. Histological examination reveals gastric atrophy with loss of glands, lymphocytic infiltration, and presence of plasma cells. Symptoms include dyspepsia, loss of appetite and loss of appetite.